2012
DOI: 10.1007/s12098-012-0899-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Hepatitis C Virus, Hepatitis B Virus, and Human Immunodeficiency Virus in Transfused Children in Kinshasa

Abstract: HCV infection was by far more frequently identified than HBV and HIV infections among Congolese transfused children. Frequency of transfusion events was the only significant risk factor associated with HCV and HIV infections but not for HBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
4
4
0
Order By: Relevance
“…This coincides with previous reports,4,12 but contradicts others 3,14,16–18. Gender does not seem a risk factor for acquiring TTI, but was unexpectedly associated with HCV seropositivity in our study; this finding was also reported elsewhere 19.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This coincides with previous reports,4,12 but contradicts others 3,14,16–18. Gender does not seem a risk factor for acquiring TTI, but was unexpectedly associated with HCV seropositivity in our study; this finding was also reported elsewhere 19.…”
Section: Discussionsupporting
confidence: 92%
“…Albeit an essential lifesaving intervention, blood transfusion carries the risk of transfusion-transmitted infections (TTIs), such as hepatitis B and C,2 which compose a major challenge to the public health worldwide 3. In general, screening blood donors with sensitive methods has reduced the incidence of TTIs 4.…”
Section: Introductionmentioning
confidence: 99%
“…HBV-positivity was relative moderate (2.4%), and was similar to previous findings from the target populations in Cameroon (4.3%) [13], and in other countries (2% in Ethiopia [22], 1.6% in Democratic republic of Congo [25], 1.2% in Tanzania [26], 2.2% in Malawi [27], 3.3% in Thailand [28]). Compared to the highly endemic HBV among adult populations [15] or pregnant women (17, 5%) [18], the relatively moderate pediatric HBV prevalence is probably due to the wide paediatric coverage of anti-HBV vaccination in Cameroon [29].…”
Section: Discussionsupporting
confidence: 87%
“…The HBsAg prevalence in HIV infected children in this study (2.0%) is comparable with studies in Thailand (3.3%), Democratic Republic of Congo (1.6%) and Tanzania (1.2%) and [ 12 , 17 , 18 ]. In contrast, it is lower compared to other studies in Africa.…”
Section: Discussionsupporting
confidence: 85%